Transparent composites prepared from bacterial cellulose and castor oil based polyurethane as substrates for flexible OLEDs - Pinto, E. R.P. [UNESP]; Barud, H. S. [UNESP]; Silva, R. R. [UNESP]; Palmieri, M. [UNESP]; Polito, W. L.; Calil, V. L.; Cremona, M.; Ribeiro, S. J.L. [UNESP]; Messaddeq, Y. [UNESP] (Royal Society of Chemistry (RSC), 2015)
Flexible and transparent composites were prepared from bacterial cellulose (BC) and castor oil based polyurethane (PU). The new BC/PU composites exhibit excellent transparency (up to 90%) in the visible region and great mechanical properties, with a tensile strength of up to 69 MPa and a Young's Modulus up to 6 GPa. The resulting free-standing thin films possessed low surface roughness (below 1 nm), and whose properties suggest a potential candidate substrate for flexible light emitting devices. Subsequently, the fabrication of flexible organic light emitting diodes (flexible OLEDs) was successfully investigated by using flexible transparent BC/PU membranes rather than standard flat glass substrates.